Matrizes históricas e jurídicas de Constituição da concentração fundiária e direito à moradia : ocupações urbanas em Passo Fundo - Lampert, Cássio Bonotto (2022)
This dissertation aimed to address historical aspects regarding the land formation in the northern region of Rio Grande do Sul. We analyzed the various forms of occupation of the territory under study, such as conquest, colonization, state policies to encourage occupation and legislation, like the Land Law. In addition, the power relations between individuals and the state were highlighted, as well as the introduction of capitalization of rural property and the formation of the city of Passo Fundo, its development following its master plans. The study focuses on urban occupations that started in late 20th century and early 21st century. Rights were analyzed as property in its relativization according to the understanding of Maria Rosa Congost Colomer, it was exposed new legal perceptions about property and new paradigms such as the right to the city, Local Power configured in Democratic Management as an instrument guarantor of the interests of several local social groups that favor the exercise of citizenship. For a closer approximation of reality, based on the city of Passo Fundo-RS, a study of the occupations of the city was carried out in order to identify its protagonists, for which newspapers and interviews were used as sources. The newspapers were analyzed according to Patrick Charaudeau's method to establish the positions of the local press in relation to the occupations of Passo Fundo. The interviews gave voice to the protagonists of the occupations and to the representatives of the Judiciary and of Human Rights, bringing to the scene the active subjects in this context called occupation. Twenty residents of four occupations in the city of Passo Fundo were interviewed, being a representative of the community, a representative of the Municipality, a representative of Human Rights and a judge who has already acted in cases related to occupations. The interviews addressed the origins, motivations, aspirations, needs and understanding of rights, all taking into account the individualities of each interviewee.